Peran Pola Asuh Orang Tua dan Kebiasaan Belajar terhadap Hasil Belajar IPA - Dasmo Dasmo; Hikmah Binoardi; Zakiah Fithah A’ini (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2011)
The purpose of this study to determine the influences of parent’s guiding and students’ learning habit as the results of science study. This study used survey method with double regretion analysis. The total number of samples as many as 200 respondents from grade VII of SMPN at Cimanggis District Depok on academic year of 2010/2011. The data were analyzed wih descriptive statitistics, data analysis, and test hypotheses used with double regretion. With the hypothesis test, which gave the results: 1) parents guiding give positive effects and significance result to out put of learning science class. 2) learning habit gives positive effect and significance to out put of leaming science class. 3) Then using double regresion analysis, it was gotten conclusion that there are positive effect and significance from both of parents guiding and also students’ learning habit to result of learning from science class. Based on that, so much better of parents guiding and much better students’ learning habit that will be done both of them, so much better their result of science class.